Strategi Bauran Promosi pada Cafe Mimici Bogor - Fahmi Khafabih, Muhamad Rois; Harini, Sri (Jurnal Riset Manajemen dan Akuntansi, 2026)
The development of globalization and digital technology has encouraged culinary SMEs to implement effective promotional strategies to remain competitive and improve sales performance. Cafe Mimici Bogor, as one of the culinary businesses, has experienced sales fluctuations, indicating that the applied promotional strategies have not been fully optimal. This study uses a descriptive qualitative approach through observation, interviews, questionnaires, and documentation to understand the implementation of the promotion mix, including promotional messages, media, and timing. The results show that promotional messages remain the main challenge, as some consumers consider the messages conveyed to be unclear and not informative. Meanwhile, social media platforms such as Instagram and TikTok are effective in reaching audiences but require improvements in content consistency and creativity. The implementation of digital promotional strategies during the Field Work Lecture Kuliah Kerja Lapangan (KKL) increased audience interactions, including views, likes, comments, and shares on social media, and positively impacted sales, which increased by 24.1% compared to the previous period. This study concludes that a structured digital promotion strategy plays a vital role in enhancing consumer understanding and marketing performance and recommends strengthening messages, media, and promotion scheduling for higher effectiveness.